2023
DOI: 10.1002/ajh.26826
|View full text |Cite
|
Sign up to set email alerts
|

Orelabrutinib in relapsed or refractory chronic lymphocytic leukemia/small lymphocytic lymphoma patients: Multi‐center, single‐arm, open‐label, phase 2 study

Abstract: BackgroundOrelabrutinib is a novel, small molecule, selective irreversible Bruton's tyrosine kinase inhibitor. The aim of this study was to evaluate the e cacy as well as safety in patients with refractory or relapsed chronic lymphocytic leukemia/small lymphocytic lymphoma (R/R CLL/SLL). MethodsThis is single-arm, multi-center, open-label, phase 2 study in 80 eligible Chinese patients, who were treated with monotherapy of orelabrutinib at 150 mg once daily. Overall response rate (ORR) that was evaluated by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Interestingly, many of these side-effects are thought to be due to off-target effects, and could theoretically be avoided by the use of compounds with higher speci city for BTK. Encouragingly, next-generation BTK inhibitors that are currently in development for chronic urticaria and autoimmune diseases are more selective for BTK with fewer off-target effects, and therefore show more favorable sideeffect pro les [22][23][24][25] . For example, 12 weeks of remibrutinib (manufacturer: Novartis) was well-tolerated in a phase 2 trial for chronic urticaria with no observed bleeding, arrhythmia, or hypertension events in the treatment arms 22 , as well as during the open-label extension of this trial for up to 52 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many of these side-effects are thought to be due to off-target effects, and could theoretically be avoided by the use of compounds with higher speci city for BTK. Encouragingly, next-generation BTK inhibitors that are currently in development for chronic urticaria and autoimmune diseases are more selective for BTK with fewer off-target effects, and therefore show more favorable sideeffect pro les [22][23][24][25] . For example, 12 weeks of remibrutinib (manufacturer: Novartis) was well-tolerated in a phase 2 trial for chronic urticaria with no observed bleeding, arrhythmia, or hypertension events in the treatment arms 22 , as well as during the open-label extension of this trial for up to 52 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Orelabrutinib is a novel BTK inhibitor, 12 which is effective in the treatment of small B‐cell lymphoma, 13 central nervous system lymphoma 14 and Fahrenheit macroglobulinaemia 15 . Although ibrutinib has been applied to several autoimmune diseases, there is no relevant data on orelabrutinib yet.…”
Section: Discussionmentioning
confidence: 99%
“…Orelabrutinib is a novel, oral, and covalent next‐generation BTK inhibitor with high target selectivity. Orelabrutinib has shown favorable efficacy and safety in other B cell malignancies and has been approved in China for the treatment of r/r chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) and r/r mantle cell lymphoma (MCL) 11,12 . To further investigate the efficacy and safety of orelabrutinib in MZL, we conducted a phase 2, multicenter, open‐label clinical trial of orelabrutinib monotherapy in patients with r/r MZL, which was the first pivotal trial of a BTK inhibitor treating r/r MZL patients conducted in China.…”
Section: Introductionmentioning
confidence: 99%